1890 Okla. Stat. 475-76, ch. 25, art. 38, §§ 18-19 - (:unkn) unknown (General Publisher, 1890)
Prohibited the manufacture, sale, giving, or disposing of any instrument or weapon usually known as a slungshot, and prohibited the carrying any slungshot or similar weapon.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS